Targeting the poor in Mexico: evaluation of the selection of beneficiary households into PROGRESA - Skoufias, Emmanuel; Davis, Benjamin; de la Vega, Sergio (International Food Policy Research Institute, 2001)
The objective of this report is to conduct a re-evaluation of the targeting methods used by PROGRESA in light of the revisions adopted by the PROGRESA administration regarding how households are selected as eligible for PROGRESA benefits. Soon after completion of the report by Skoufias, Davis and Behrman in June 1999 we were informed that PROGRESA had added new households to the list of beneficiaries through a process called densification" since it was felt that the original selection method was biased against the elderly poor who no longer lived with their children. As a result of the “densification” process the percent of households classified as eligible for program benefits increased from 52% of the sample to 78% of the sample. Given this large expansion in the number of eligible households it was felt that it is imperative to re-evaluate the targeting methods used by PROGRESA by adopting the same approach and methods used in the June 1999 report. Under the circumstances the June 1999 report should be considered as more relevant for providing detailed information about the methods used to evaluate PROGRESA’a targeting whereas this report should be considered as containing the definitive results of the evaluation of PROGRESA’s targeting methods. PROGRESA’s methodology consists of three stages: (1) the selection of localities; (2) the selection of beneficiary households within selected localities, and (3) finalizing the list of beneficiaries after feedback from the community assemblies about families excluded or included incorrectly. We evaluate in detail the first two stages of the selection process. We do not provide an evaluation of the third stage of selection as the number of households whose selection into PROGRESA was disputed at this stage of the selection process was minute (0.1% of the total number of selected households). Our evaluation is based on a framework consisting of three key elements: (i) a social objective, (ii) a set of economic, political and social constraints under which policy has to operate, and (iii) a range of instruments available to attain these objectives. Although PROGRESA has a number of interlinked objectives with respect to health, education and nutrition, we will measure the benefits of PROGRESA’s targeting solely in terms of its potential impact on poverty alleviation."